Criteria Identification For Returning To Sport After Achilles Tendon Injury (International Journal of Physiotherapy, 2021)
Background: The Achilles tendon rupture is a pathology of growing incidence due to the increase in the intensity of amateur sports practices and the continuation of this practice with the rise in age. The rupture follows a degradation of the tendon’s structure, known as degenerative tendinopathy, which is symptomatic only in rare cases. In the absence of prior pain, iterative rupture is the complication to be feared and prevented. Unfortunately, after orthopedic or surgical treatment, there is no consensus concerning criteria for returning to sports. Such criteria would aim to prevent the risk of recurrence and the appearance of other sports injuries.Methods: A current literature review using the PubMed database in June 2021.Results: The literature doesn’t show any validated criteria for returning to sport.Conclusion: Consequently, this work seeks to propose objective criteria for validating the return to sport in connection with the physical and psychological qualities of the subject, abrogating temporal criteria, too formal and remote from the clinical view. Thus, the physiotherapist is advised to take an interest in the ankle's range of motion and the stiffness of the tendon, strength and endurance of the calf muscle, the quality of the proprioceptive and postural functions on a more functional plan, based on the quality of the jumps and then on the subject's running pattern. Finally, a psychological assessment completes the battery of tests that will validate the return to sport.